Pediococcus pentosaceus: Screening and Application as Probiotics in Food Processing - Qi, Yining; Huang, Le; Zeng, Yan; Li, Wen; Zhou, Diao; Xie, Jianhua; Xie, Junyan; Tu, Qiang; Deng, Dun; Yin, Jia (Frontiers in Microbiology, 2021)
Lactic acid bacteria (LAB) are vital probiotics in the food processing industry, which are widely spread in food additives and products such as meat, milk and vegetables. Pediococcus pentosaceus (P. pentosaceus), as a kind of LAB, has numerous probiotic effects, mainly including antioxidant, cholesterol-lowering and immune effects. Recently, the applications in the probiotic- fermentation products have attracted progressively more attentions. However, it is necessary to screen P. pentosaceus with abundant functions from diverse sources due to the limitation about the source and species of P. pentosaceus. This review summarized the screening methods of P. pentosaceus and the exploration methods of probiotic functions in combination with the case study. The screening methods included primary screening and rescreening including gastric acidity resistance, bile resistance, adhesion, antibacterial effects, etc. The application and development prospects of P. pentosaceus were described in detail, and the shortcomings in the practical application of P. pentosaceus were evaluated to make better application of P. pentosaceus in the future.